Exposure to Morphine and Caffeine Induces Apoptosis and Mitochondrial Dysfunction in a Neonatal Rat Brain - Kasala, Sweatha; Briyal, Seema; Prazad, Preetha; Ranjan, Amaresh K.; Stefanov, Gospodin; Donovan, Ramona; Gulati, Anil (Frontiers in Pediatrics, 2020)
Background: Preterm infants experience rapid brain growth during early post-natal life making them vulnerable to drugs acting on central nervous system. Morphine is administered to premature neonates for pain control and caffeine for apnea of prematurity. Simultaneous use of morphine and caffeine is common in the neonatal intensive care unit. Prior studies have shown acute neurotoxicity with this combination, however, little information is available on the mechanisms mediating the neurotoxic effects. The objective of this study was to determine the effects of morphine and caffeine, independently and in combination on mitochondrial dysfunction (Drp1 and Mfn2), neural apoptosis (Bcl-2, Bax and cell damage) and endothelin (ET) receptors (ETA and ETB) in neonatal rat brain. Methods: Male and female rat pups were grouped separately and were divided into 4 different subgroups on the basis of treatments - saline (Control), morphine (MOR), caffeine (CAFF), and morphine + caffeine (M+C) treatment. Pups in MOR group were injected with 2mg/kg morphine, CAFF group received 100mg/kg caffeine, and M+C group received both morphine (2mg/kg) and caffeine (100mg/kg), subcutaneously on postnatal days (PND) 3-6. Pups were euthanized at PND 7, 14, or 28. Brains were isolated and analyzed for mitochondrial dysfunction, apoptosis markers, cell damage and ET receptor expression via immunofluorescence and western blot analyses. Results: M+C showed a significantly higher expression of Bax compared to CAFF or MOR alone at PND 7, 14, 28 in female pups (p<0.05) and at PND 7, 14 in male pups (p<0.05). Significantly (p<0.05) increased expression of Drp1, Bax and suppressed expression of Mfn2, Bcl-2 at PND 7, 14, 28 in all the treatment groups compared to the control was observed in both genders. While, no significant difference in the expression of ETA and ETB receptors in male or female pups was seen at PND 7, 14 and 28. Conclusion: Concurrent use of morphine and caffeine during the first week of life increases apoptosis and cell damage in the developing brain compared to individual use of caffeine and morphine.